Spatial proximity between two host plant species influences oviposition and larval distribution in a leaf beetle - Ballabeni, Pierluigi; Conconi, Davide; Gateff, Sophie; Rahier, Martine (My University, 2001)
Everything else being equal, insect herbivores can be expected to oviposit on host plants that provide the qualitatively and quantitatively best food for larvae. However, the selection of a plant for oviposition may be influenced by such ecological factors as natural enemies, host distribution, host patch size or host patch density. We performed a field study to test whether spatial proximity between two host plant species influences the oviposition patterns and larval distribution of the alpine leaf beetle Oreina elongata. In the population studied, O. elongata oviposits and feeds on two host plants, that belong to the same family (Asteraceae): Adenostyles alliariae and Cirsiumspinosissimum. The first species contains pyrrolizidine alkaloids that are sequestered by the beetle as a chemical defence, whereas the second plant does not contain any alkaloids but has hairy and spiny leaves that might give some mechanical protection to beetle larvae.
During two consecutive summers, we quantified oviposition and larval distribution on randomly chosen C. spinosissimum that grew spatially isolated from A. alliariae, on C. spinosissimum that grew in leaf contact with A. alliariae and on A. alliariae that grew in leaf contact with C. spinosissimum (isolated A. alliariae was not considered, because it is rare in the study population). In both years, more eggs were laid on C. spinosissimum than on A. alliariae and more on those C. spinosissimum that were growing close to A. alliariae than on those growing isolated. Large numbers of larvae moved from C. spinosissimum to A. alliariae during the season. Patch size did not influence egg and larval numbers. Eggs survived better on C. spinosissimum than on A. alliariae in the field. The data suggest that C. spinosissimum may provide eggs with better protection against stormy weather. In a separate study of the same population, we found that larval performance was better on A. alliariae than on C. spinosissimum. Our present data suggest that O. elongata preferentially oviposits on plants of the species that maximizes egg survival and that grow in close proximity to plants of the species that provides better food and chemical defence.